Ultrastructural features of canine neuroaxonal dystrophy in a Papillon dog - TANAKA, Miyuu (J Vet Med Sci, 2017)
Neuroaxonal dystrophy (NAD) is a neurodegenerative disease characterized by severe axonal swelling (spheroids) throughout the nervous system. In dogs, NAD has been reported in several breeds and a missense mutation in PLA2G6 gene has recently been identified in the Papillon dog NAD. Here we performed ultrastructural analysis to clarify the detailed ultrastructural features of the Papillon dog NAD. Dystrophic axons consisted of accumulation of filamentous materials, tubulovesicular structures, and swollen edematous mitochondria with degenerated inner membranes were often observed in the central nervous system. At axonal terminals, degeneration of presynaptic membrane was also detected. As reported in Pla2g6 knockout mice, mitochondrial and presynaptic degeneration may be related with the pathogenesis of NAD in Papillon dogs.